The characterization of the Phlebotomus papatasi transcriptome. Issue 2 (7th February 2013) - Abrudan, J.; Ramalho‐Ortigão, M.; O'Neil, S.; Stayback, G.; Wadsworth, M.; Bernard, M.; Shoue, D.; Emrich, S.; Lawyer, P.; Kamhawi, S.; Rowton, E. D.; Lehane, M. J.; et al.
Abstract As important vectors of human disease, phlebotomine sand flies are of global significance to human health, transmitting several emerging and re‐emerging infectious diseases. The most devastating of the sand fly transmitted infections are the leishmaniases, causing significant mortality and morbidity in both the Old and New World. Here we present the first global transcriptome analysis of the Old World vector of cutaneous leishmaniasis, Phlebotomus papatasi (Scopoli) and compare this transcriptome to that of the New World vector of visceral leishmaniasis, Lutzomyia longipalpis. A normalized cDNA library was constructed using pooled mRNA from Phlebotomus papatasi larvae, pupae, adult males and females fed sugar, blood, or blood infected with Leishmania major. A total of 47 615 generated sequences was cleaned and assembled into 17 120 unique transcripts. Of the assembled sequences, 50% (8837 sequences) were classified using Gene Ontology (GO) terms. This collection of transcripts is comprehensive, as demonstrated by the high number of different GO categories. An in‐depth analysis revealed 245 sequences with putative homology to proteins involved in blood and sugar digestion, immune response and peritrophic matrix formation. Twelve of the novel genes, including one trypsin, two peptidoglycan recognition proteins (PGRP) and nine chymotrypsins, have a higher expression level during larval stages. Two novel chymotrypsins and one novel PGRP are abundantly expressed upon blood feeding. This study will greatly improve the available genomic resources for P. papatasi and will provide essential information for annotation of the full genome.